Acquired perforating dermatosis in a patient with chronic renal failure - Karen de Almeida Pinto Fernandes; Lourenço de Azevedo Lima; Juliana Chaves Ruiz Guedes; Ricardo Barbosa Lima; Antônio Macedo D'Acri; Carlos José Martins (Sociedade Brasileira de Dermatologia, 2016)
Abstract Perforating dermatoses are a group of skin diseases characterized by transepidermal elimination of dermal material. The disease is divided into two groups: the primary group and the secondary group. The classical or primary perforating dermatoses are subdivided into four types according to the eliminated dermal materials: Kyrle disease, perforating reactive collagenosis, elastosis perforans serpiginosa, and perforating folliculitis. The secondary form is known as acquired perforating dermatosis. The term was proposed in 1989 by Rapini to designate the perforating dermatoses affecting adult patients with systemic disease, regardless of the dermal materials eliminated. This report describes a case of the disease with elimination of collagen and elastic fibers in a patient with chronic renal failure.